2018
DOI: 10.1016/j.jspd.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Versus High-Dose Postoperative Naloxone Infusion Combined With Patient-Controlled Analgesia for Adolescent Idiopathic Scoliosis Surgery: A Randomized Controlled Trial

Abstract: Level 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Overall, the use of IV naloxone is not associated with any significant changes in opioid consumption nor with the risk of sedation or emesis [3,44]. In other more recent study, low and ultra-low doses such as 0.25 µg/kg are also reported to reduce pain intensity due to morphine consumption, pruritus and nausea [45,46]; finally, Pieters [47] found that a high dose naloxone of 0.5 mg/kg/h was not more efficient in reducing opioid side effects, despite partially reversing the analgesic effect of opioid by yielding an increase in demand on postoperative day 2.…”
Section: Side Effects Of Iv-pcamentioning
confidence: 90%
See 1 more Smart Citation
“…Overall, the use of IV naloxone is not associated with any significant changes in opioid consumption nor with the risk of sedation or emesis [3,44]. In other more recent study, low and ultra-low doses such as 0.25 µg/kg are also reported to reduce pain intensity due to morphine consumption, pruritus and nausea [45,46]; finally, Pieters [47] found that a high dose naloxone of 0.5 mg/kg/h was not more efficient in reducing opioid side effects, despite partially reversing the analgesic effect of opioid by yielding an increase in demand on postoperative day 2.…”
Section: Side Effects Of Iv-pcamentioning
confidence: 90%
“…Opioid infusions in children are useful, but adequate dosing and titration require careful supervision. Nevertheless, morphine titration in pediatrics has limitations, as pain scores are not always obtainable in the PACU and the validity of self-reported pain intensity scores may be unreliable in children with developmental and neurological disabilities, thereafter affecting the analgesic protocol and necessitating close monitoring [47,48].…”
Section: Pca In Childrenmentioning
confidence: 99%
“…A retrospective study conducted by Pieters et al [31] reported ten kids who were administered IT morphine. All patients received lumbar intrathecal injections of preservative-free morphine (Duramorph®) at a dose of 0.02 mg/kg prior to the start of surgery.…”
Section: Effect Of Epidural and Intrathecal Morphine 3611 In Childrenmentioning
confidence: 99%
“…Of note, investigations using IV naloxone (0.5mcg/kg/hr) to mitigate opioid-related side effects of pruritis, nausea, vomiting, and respiratory depression have shown limited efficacy against pruritis and nausea, but other outcomes were nonsigificant. [8][9] Considering the high incidence of PONV and pruritis, other techniques described later in this review have been investigated to supplement IV PCA to minimize morphine use.…”
Section: Morphinementioning
confidence: 99%